A systematic review of the interventions to promote the wearing of hearing protection - Dib, Regina Paolucci El; Atallah, Álvaro Nagib; Andriolo, Régis Bruni; Soares, Bernardo Garcia de Oliveira; Verbeek, Jos H. (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Noise-induced hear- ing loss can only be prevented by eliminating or lowering noise exposure levels. When the source of the noise cannot be eliminated, workers have to rely on hearing protection equipment. The aim here was to summarize the evidence for the effectiveness of interventions to enhance the wearing of hearing protection among workers exposed to noise in the workplace. DATA SOURCE: Studies with random assignment were identiﬁed by an electronic search of the medical literature up to 2005. Data were dou- ble-entered into the Review Manager software, version 4.2.5. DATA SYNTHESIS: Two studies were found. A computer-based intervention tailored to individual workers’ risks and lasting 30 minutes was not found to be more effective than a video provid- ing general information for workers. A second randomized controlled trial evaluated the effect of a four-year school-based hearing loss prevention program among schoolchildren working on their parents’ farms. The intervention group was twice as likely to wear some kind of hearing protection as was the control group (which received only minimal intervention). REVIEWERS’ CONCLUSIONS: The limited evi- dence does not show whether tailored interven- tions are more or less effective than general interventions among workers, 80% of whom already use hearing protection. Long-lasting school-based interventions may increase the use of hearing protection substantially. Better inter- ventions to enhance the use of hearing protection need to be developed and evaluated in order to increase the prevention of noise-induced hearing loss among workers.